Morphological Characterization of Soil Penicillium sp. Strains - Potential Producers of Statin - Seydametova, Emine (2010)
At present time, search for fungal species of Penicillium genus – potential producers of biotechnologically valuable metabolites, has gained considerable momentum. The aim of present study was to examine the fungal isolates from soils of Pahang state, proposed to belong to Penicillium genus. Twenty fungal cultures were examined for characters of morphology. The variables used in this study were macromorphological characters: colony diameter, obverse and reverse colony colour, and the presence or absence of exudates. Moreover, microscopic characteristics of the fungal isolates were examined using an optical microscope. The colony appearance of each fungal isolate was characterized on different agar media: CZ, CYA, YES, MEA. The macro- and micromorphological characters of isolated cultures appeared to be distinctive. Based on colony macromorphology, as well as the structure of conidiophores, it was revealed that fungal isolates belong to Penicillium genus. Results of this research have demonstrated that some soils in Pahang state can be considered as a valuable natural source of filamentous fungi from Penicillium genus.